1989
DOI: 10.1073/pnas.86.20.8055
|View full text |Cite
|
Sign up to set email alerts
|

Presence of maternal antibodies to human immunodeficiency virus 1 envelope glycoprotein gp120 epitopes correlates with the uninfected status of children born to seropositive mothers.

Abstract: The present study demonstrates that maternal antibodies to certain epitopes of human immunodeficiency virus 1 (HIV-1) proteins are associated with a defined outcome for at-risk pregnancies of HIV-infected women. An initial retrospective analysis of antibodies to synthetic peptides and recombinant proteins representing env, pol, and gag regions of HIV-1 was carried out. Sera studied were from 33 children who were born to HIV-infected mothers and whose clinical outcome was known at the time of analysis. Sera, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(71 citation statements)
references
References 30 publications
4
65
1
1
Order By: Relevance
“…Sequences spared by antibodies of natural immunity are potential candidates for an antibodyresistant fractionated vaccine if such sequences can induce neutralizing antibodies. In human immunodeficiency virus infections, it was shown that natural immunity does not involve all possible immunogenic peptides, leaving some capable of by-passing natural antibodies (Rossi et al, 1989). Further studies however are necessary to show, firstly, whether synthetic peptides can elicit neutralizing antibodies against measles virus F protein and, secondly, whether a peptide cocktail can be designed which is (partially) resistant to (maternal) antimeasles virus antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Sequences spared by antibodies of natural immunity are potential candidates for an antibodyresistant fractionated vaccine if such sequences can induce neutralizing antibodies. In human immunodeficiency virus infections, it was shown that natural immunity does not involve all possible immunogenic peptides, leaving some capable of by-passing natural antibodies (Rossi et al, 1989). Further studies however are necessary to show, firstly, whether synthetic peptides can elicit neutralizing antibodies against measles virus F protein and, secondly, whether a peptide cocktail can be designed which is (partially) resistant to (maternal) antimeasles virus antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Infant A2 developed pneumococcal meningitis at 18 wk ofage. Infant A3 was evaluated at 9 wk ofage for fever of unknown origin, oral candidiasis, and lymphadenopathy, and developed Pneumocystis carinii and cytomegalovirus pneumonia at 14 Sequences of HIV-I env VI -V2-C2 region were amplified using the PCR and nested oligonucleotide primers prepared in the DNA synthesis core facility of the Interdisciplinary Center for Biotechnology Research at the University of Florida. The outer primers were ENV5 (5'-GGTAGAACAGATGCATGAGGAT-3') and ENV6 (5'-CCA-TGTGTACATTGTACTGTGCT-3'), located at nucleotides 6102-6123 and 6544-6566 in the genome of HIVLAI (27).…”
Section: Methodsmentioning
confidence: 99%
“…Mother-to-child transmission of HIV-1 is undoubtedly multifactorial, although the factors that contribute to, or inhibit, maternal transmission of HIV-1 are not completely defined ( 11 ). Because passive maternal antibody is the primary immunity that a fetus acquires, it is likely that maternal humoral immunity is one factor in vertical transmission of HIV-1 (12)(13)(14)(15). However, the specificities of maternal antibodies that can protect against HIV-1 transmission are unclear (16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Peptide and peptide ELISA A linear peptide, C53, containing 15 amino acids was used as antigen in an ELISA as described previously [20]. The peptide had sequences of the BHIO clone derived from the HIV-1/ HTLVIIIB isolate and represented the V3 region (amino acids 304-318) of gpl20.…”
Section: Neutralization Assaymentioning
confidence: 99%